Burden of pulmonary tuberculosis among tribal population: A cross-sectional study in tribal areas of Maharashtra, India - Anil J Purty; Amit Kumar Mishra; Ramesh Chand Chauhan; Rajendran Prahankumar; Prabakaran Stalin; Joy Bazroy (Wolters Kluwer Medknow Publications, 2019)
Background: It is very important to identify and treat infectious pulmonary tuberculosis (PTB) patients at the earliest to save the life of the patients and to prevent the transmission of infectious agent to others. As per Global Tuberculosis (TB) Report 2017, an estimated 28 lakh new TB cases occur and 4.23 lakh people die due to TB annually. Due to the poor health services and lack of awareness, particularly vulnerable tribal groups are vulnerable or at risk to many diseases including TB. Methodology: A community-based cross-sectional study was conducted to determine the burden of pulmonary TB (PTB) among adult tribal population of Maharashtra. House-to-house visit was conducted to identify the presumptive TB cases and sputum microscopy and chest X-ray were done to confirm the diagnosis. Results: In the survey, 6898 tribal adults were interviewed from 8 tribal clusters, and among them, 144 (2.1%) presumptive TB cases were identified. The most common symptom among the presumptive TB cases was cough for >2 weeks (93.1%). The prevalence of PTB in the study area estimated is 261per lakh tribal population per year. Conclusion: The current study shows that the estimated burden of PTB among tribal population is within the wide variation of prevalence reported from other studies in different tribal communities (133-3294 per lakh population) in India. The current study provides vital information on the burden of TB among the tribal population of Maharashtra which can be used as a baseline data for future epidemiological studies.